2022
DOI: 10.7150/thno.66059
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of interaction between LOXhigh fibroblast and smooth muscle cells contributes to the pathogenesis of aortic dissection

Abstract: Rationale: While cell-cell interaction plays a critical role in physiology and disease, a comprehensive understanding of its dynamics in vascular homeostasis and diseases is yet absent. Methods: Here, by use of single-cell RNA-sequencing and multi-color staining, we delineate the cellular composition and spatial characterization of human aorta with or without aortic dissection (AD). Results: Scrutinization of cell subtype alterations revealed significantly changed fibroblast (FB)-smooth muscle cell (SMC) inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…At present, there is little literature on BMP involvement in AD. In a recent study, BMP inhibition by LDN-193189, a potent selective BMP type I receptor (BMPR I) inhibitor, significantly reduced maximal ascending aorta diameter and systolic blood pressure in 3aminopropionitrile fumarate (BAPN)-and Ang II-treated mice (Chen et al, 2022). Most importantly, LDN-193189 treatment decreased the incidence of AD by 70% (Chen et al, 2022).…”
Section: The Bmp Family and Aortic Dissection (Ad)mentioning
confidence: 99%
“…At present, there is little literature on BMP involvement in AD. In a recent study, BMP inhibition by LDN-193189, a potent selective BMP type I receptor (BMPR I) inhibitor, significantly reduced maximal ascending aorta diameter and systolic blood pressure in 3aminopropionitrile fumarate (BAPN)-and Ang II-treated mice (Chen et al, 2022). Most importantly, LDN-193189 treatment decreased the incidence of AD by 70% (Chen et al, 2022).…”
Section: The Bmp Family and Aortic Dissection (Ad)mentioning
confidence: 99%
“…By conducting comparative GO analysis, we studied the biological implication of TAA and AAA-related upregulated DEGs and found that both h Fibromyocyte and m SMC4 enriched for cell chemotaxis and cell–cell adhesion in the TAA group compared with AAA group; m SMC4 in TAA and AAA exhibited similar enrichment for collagen fibril organization, ossification, and cell adhesion ( Figure 3E ; Supplementary Figure S4D ). In both organisms, we uncovered that CXCL12 , MFAP5 , and EMP1 might participate in the pathogenesis of AAA, among which it had been reported that the blockade of CXCL12/CXCR4 protected against AAA formation ( Michineau et al, 2014 ), whereas several collagen genes ( COL1A1 , COL1A2 , COL3A1 , and COL5A2 ); some reported virulence genes for TAA ( LOX , COL3A1 , and MMP2 )( Longo et al, 2002 ; Shen et al, 2015 ; Pinard et al, 2019 ; Chen et al, 2022 ); and potential causative genes ( CTHRC1 , SERPINH1 , SPARC , THY1 , and CTSK ) were identified involving in the pathology of TAAs ( Figure 3F ).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, in TAA and AAA, we identify distinct marker genes as potential regulators participating in the pathological process in both organisms. For example, both in h Fibromyocyte and m SMC3, we identify potential causative genes for AAA ( CXCL12 , MFAP5 , and EMP1 ), among which the blockade of CXCL12/CXCR4 protects against AAA formation ( Michineau et al, 2014 ), and distinct pathogenic genes for TAA [collagen genes ( COL1A1 , COL1A2 , COL3A1 , and COL5A2 ), some reported virulence genes for TAA ( LOX , COL3A1 , and MMP2 ) ( Longo et al, 2002 ; Shen et al, 2015 ; Pinard et al, 2019 ; Chen et al, 2022 ), and other unreported genes ( CTHRC1 , SERPINH1 , SPARC , THY1 , and CTSK )]. Among the genes we enriched, the presence of these proven disease-causing genes to some extent supported the validity of our analysis, and the role of these unreported genes deserved further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The primary molecular traits of different cell types can also be further resolved, enabling higher resolution identification between different subtypes of the same cell to reveal functional differences. This can then lead to an in-depth study and interpretation of mechanisms that might be present in AAD, such as intercellular interactions ( 112 ). Another scRNA-seq-based investigation identified seven main DEGs (ACTA2, IL6, CTGF, BGN, ITGA8, THBS1, and CDH5) and significant alterations in the relative number of VSMCs.…”
Section: Discovery Of Aad Biomarkers Based On Multi-omics Technologiesmentioning
confidence: 99%